Jejaring Kebijakan dalam Perumusan Implementasi Kebijakan Online Single Submission (OSS) dalam Perizinan Usaha di DPMPTSP Kota Tanjungpinang - Futra; Wahyu Nugroho; Daffa Anugrah (Policy, Law and Political Research Center, 2022)
Policies that are present have contributed to driving the nation's economy. With Presidential Regulation Number 91 of 2017 the government issued a policy to speed up and facilitate business services by using the Electronically Integrated Business Licensing System (Online Single Submission). The problems with the Online Single Submission (OSS) at the Tanjungpinang City Investment and One-Stop Integrated Services Service are, first, the network at the center is often disturbed so that it is difficult for regions to access OSS. The licensing database in OSS has not been clearly classified, so regions have to sort out data again and enter data manually which causes the process of issuing a permit to take a long time. The purpose of this study is to provide an explanation in the government network which is a form of public sector collaboration. The method used is qualitative based on two sources of primary and secondary data in the form of interviews, institutional databases, websites, and previous research. The results show that the OSS system in Tanjungpinang City has had a positive impact on business actors, with the convenience offered by the OSS system, many Micro Enterprises have been built using the OSS system management service. However, there are still obstacles, such as the absence of a Regional Regulation that regulates in more detail the application of the system, so there is a need for an in-depth analytical study so that the use of the OSS system can be used more effectively with more binding derivative rules.